Restoration of Transient Electromagnetic Signal Based Incremental Wiener Filter - Haiming Yan; Guofu Wang; Faquan Zhang; Jincai Ye (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Duo to the effect of receiving antenna, there is a certain deviation between the transient electromagnetic signal and the observation signal outputted from receiving antenna, leading to large blind areas in the shallow exploration of TEM. In order to improve the distortion of the outputted signal, the algorithm of deconvolution based on incremental wiener filter is proposed to recovery the signal in this paper. The influence of receiving antenna to transient electromagnetic signal is eliminated, and the optimum estimated is obtained after the algorithm is applied to realize the deconvolution of observation signal. Theoretical analysis and experimental results show that: compared with traditional damping matching method, the recovery signal by the algorithm has a better approximation to the theoretical signal, a higher resolution in shallow exploration, and the damping state of antenna has no influence on the recovery signal. It is of importance for improving transient electromagnetic shallow exploration. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3249